What is strategy? A study in business news and institutional texts from large Brazilian companies (Comunicação & Inovação, 2022)
In this article, we discuss the relationship between communication and organizational strategy, emphasizing the meaning of strategy in news and reports published in Exame magazine and in institutional texts from large Brazilian companies. From the social systems theory's perspective, we apply semantic analysis to explore the condensation of meanings into semantic forms. The results indicate that meanings about organizational strategy produced in the relationship between organizational systems and the media system, constituting a proper semantics for strategy communication.
Keywords: organizational communication; organizational strategy; semantic analysis